PEMETAAN TINGKAT KEBISINGAN YANG DITIMBULKAN OLEH MESIN PENGOLAH KELAPA SAWIT DI PT. TASMA PUJA, KABUPATEN KAMPAR-RIAU - Ade saputra; Defrianto '; Tengku Emrinaldi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The mapping noise levels generated by the palm oil processing machine in PT. Tasma Puja Kab. Kampar, Riau by using grid method has been conducted . The result was the noise intensity of the lowest to the highest one at 121 points in a safe area. The intensity was described in mapping using "Software Surfer 11", which generates the contour then combine with the location of PT. Tasma Puja indicated by different colors: black, blue, sky blue, green, yellow, red and purple. The highest intensity was located at the coordinates N 010 18.735 and E 1010 01.204, 98 dB was indicated by the color purple which the temperature reaches 400C, the lowest noise intensity is N 010 18.710 and E 1010 01.172 and 46 dB shown by the black color where the temperature reaches 290C. The higher temperature is due to the higher the intensity of the noise. The lower air temperature will have the lower the intensity noise. Based on the results at PT. Tasma Puja, there are several locations has exceeded the value of the noise quality standards established by the labor minister's decision number: KEP-51 / MEN / 1999. i,e 85 dB.